Air-sea interaction properties in the eastern Arabian Sea during active phase of off-shore trough (IOP 7-9 August ARMEX-2002) - CHINTHALU, G. R.; NAGAR, S. G.; SEETARAMAYYA, P. (MAUSAM, 2005)
During southwest monsoon season, the off-shore troughs along the west coast (WC) of India occupy shallow zones of convergence. These troughs frequently develop and decay off the WC extending from North Kerala to South Gujarat. They are typical in size, horizontal extent being of the order of 100 km and are discernible from just above the boundary level to about 900 hPa. They produce heavy rainfall over the coastal stations during active phase of the monsoon and vice-versa in weak phase. In the present study the transfer of surface fluxes across the air–sea interface over eastern Arabian Sea following an intense off-shore trough is examined. This trough has developed off the WC during 7-9 August 2002. The results are discussed in relation to synoptic movement of this off-shore trough on the sea level chart.